2002
DOI: 10.3354/meps244247
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical areas and habitat preferences of bottlenose dolphins Tursiops truncatus

Abstract: We present the findings of a 2-yr study of habitat use by bottlenose dolphins in the outer Shannon estuary on the west coast of Ireland. Data were collected during repeated, standardised, boat-based surveys of dolphins in a predefined 150 km 2 area of the outer estuary. Areas found to exceed a uniform-use pattern were termed 'critical areas' and delimited using the 50% contour derived from harmonic mean transformation of sighting locations. Dolphins exhibited preferential use of areas of the estuary with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
139
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(156 citation statements)
references
References 27 publications
15
139
0
2
Order By: Relevance
“…Perhaps the use of SLP /CB solely by resident dolphins indicates resource partitioning, a behavior also noted in other dolphins that seasonally inhabit bays (Ingram and Rogan, 2002). Therefore, the foraging behavior observed in each area could be merely an artifact of the bottom characteristics of the area, and these in turn may differ between resident and Gulf dolphins because of their exclusive use of each area.…”
Section: Henderson and Wursig-dolphin Behaviorpatierns In San Luis Pamentioning
confidence: 95%
See 2 more Smart Citations
“…Perhaps the use of SLP /CB solely by resident dolphins indicates resource partitioning, a behavior also noted in other dolphins that seasonally inhabit bays (Ingram and Rogan, 2002). Therefore, the foraging behavior observed in each area could be merely an artifact of the bottom characteristics of the area, and these in turn may differ between resident and Gulf dolphins because of their exclusive use of each area.…”
Section: Henderson and Wursig-dolphin Behaviorpatierns In San Luis Pamentioning
confidence: 95%
“…Environmental factors such as sea temperature, tidal activity, depth, seafloor slope, and sediment type can also affect cetacean behavior (Wiirsig and Wursig, 1979;Ingram and Rogan, 2002;Hastie et al, 2004). Several studies have demonstrated an increase in the foraging activity of bottlenose dolphins in deep channel areas with steep slopes (Wilson et al, 1997;Ingram and Rogan, 2002), This increase in foraging may indicate a higher concentration of prey as they bottleneck in narrow channels, or perhaps the steep slopes aid dolphins in herding and catching fish.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the core areas may be regarded as critical habitats for conservation (e.g. Ingram and Rogan, 2002;Karczmarski et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1987: Wilson et aJ. 1999: Ingram and Rogan 2002. However, th e size of the stud y site alone cannot acco unt for th e large num ber of transient dolphins recogni zed during th e sur veys.…”
Section: Residency and Site Fid Elit Y In The Main Areamentioning
confidence: 99%